Indirect in vitro Regeneration of the Medicinal Plant, Aspilia africana, and Histological Assessment at Different Developmental Stages - Okello, Denis; Yang, Sungyu; Komakech, Richard; Chung, Yuseong; Rahmat, Endang; Gang, Roggers; Omujal, Francis; Lamwaka, Alice V.; Kang, Youngmin (Frontiers in Plant Science, 2021)
The medicinal plant, Aspilia africana has been traditionally used in several African countries to treat many diseases including tuberculosis, cough, inflammation, malaria, osteoporosis, and diabetes. In this study, we developed a protocol for in vitro propagation of A. africana using indirect shoot organogenesis from leaf and root explants of in vitro-grown seedlings and assessed the tissues at different developmental stages. The highest callus induction (91.9 ± 2.96%) from leaf explants was in Murashige and Skoog (MS) medium augmented with 1.0 mg/L 6-Benzylaminopurine (BAP) and 1.0 mg/L 2, 4-Dichlorophenoxyacetic acid (2, 4-D) while from root explants, the highest callus induction (92.6 ± 2.80%) was in the same plant tissue culture medium augmented with 0.5 mg/L BAP and 1.0 mg/L 2, 4-D. The best shoot regeneration capacity from leaf-derived calli (80.0 ± 6.23% regeneration percentage and 12.0 ± 6.23 shoots per callus) was obtained in medium augmented with 1.0 mg/L BAP and 0.05 mg/L α-Naphthaleneacetic acid (NAA); the best regeneration capacity for root-derived calli (86.7 ± 6.24% shoot regeneration percentage and 14.7 ± 1.11 shoots per callus) was obtained in MS medium augmented with 1.0 mg/L BAP, 0.05 mg/L NAA and 0.1 mg/L Thidiazuron (TDZ). Regenerated plantlets developed a robust root system in 1/2 MS medium augmented with 0.1 mg/L NAA and had a survival rate of 93.6% at acclimatization. The in vitro regenerated stem tissue was fully differentiated, while the young leaf tissue consisted of largely unorganized and poorly differentiated cells with large intercellular air spaces typical of in vitro leaf tissues. Our study established a protocol for the indirect regeneration of A. africana and offers a basis for its domestication, large-scale multiplication, and germplasm preservation. This study to the best of our knowledge is the first to develop an indirect regeneration protocol for A. africana and conduct anatomical assessment through the different stages of development from callus to a fully developed plantlet.